2009
DOI: 10.2343/geochemj.1.0005
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative scavenging of cerium on hydrous Fe oxide: Evidence from the distribution of rare earth elements and yttrium between Fe oxides and Mn oxides in hydrogenetic ferromanganese crusts

Abstract: The distribution of the rare earths and yttrium (REY) in co-existing hydrous Mn oxides and Fe oxides that form marine hydrogenetic ferromanganese crusts is used to better describe the partitioning and fractionation of the REY between these (hydr)oxides and seawater in the natural marine system. Four fractions (easily exchangeable, Mn-oxide-bound, Fe-oxidebound, and insoluble-residue-bound REY) were separated by an adjusted sequential leaching procedure from two ferromanganese crusts from the Central Pacific. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 360 publications
(187 citation statements)
references
References 48 publications
10
174
0
3
Order By: Relevance
“…The different charge of metal complexes determines the adsorption behaviour onto the solid surfaces (Koschinsky and Hein, 2003). Bau and Koschinsky (2009) show that the Y/Ho ratio in marine Fe-Mn hydroxydes is significantly lower than seawater, suggesting an enhanced scavenging of Ho with respect to Y in the Fe-Mn crusts. Recently, Schmidt et al (2014) investigating the fractionation of Zr-Hf between seawater and Fe-Mn crusts, showed that Zr/Hf ratio is lower in the Fe-Mn oxyhydroxides compared to seawater.…”
Section: The Behaviour Of Twin Pairs (Y-ho; Zr-hf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The different charge of metal complexes determines the adsorption behaviour onto the solid surfaces (Koschinsky and Hein, 2003). Bau and Koschinsky (2009) show that the Y/Ho ratio in marine Fe-Mn hydroxydes is significantly lower than seawater, suggesting an enhanced scavenging of Ho with respect to Y in the Fe-Mn crusts. Recently, Schmidt et al (2014) investigating the fractionation of Zr-Hf between seawater and Fe-Mn crusts, showed that Zr/Hf ratio is lower in the Fe-Mn oxyhydroxides compared to seawater.…”
Section: The Behaviour Of Twin Pairs (Y-ho; Zr-hf)mentioning
confidence: 99%
“…9) shows the simultaneous variation of these elements, with the involvement of Fe and Al controlling the abundance of REE dissolved in water. Strong processes of scavenging occur during the co-precipitation and/or adsorption onto the surface of oxide and oxyhydroxide of Fe, Al, and Mn (Censi et al, 2007;Bau and Koschinsky, 2009). …”
Section: Ree Behaviourmentioning
confidence: 99%
“…These studies have drawn from a sound understanding of REE+Y cycling in modern anoxic basins. In general, oxygenated marine settings display a strong negative Ce anomaly when normalised to a shale composite (Ce (SN) ), because oxidation of Ce(III) to Ce(IV) greatly reduces Ce solubility, resulting in its preferential removal onto Mn(IV)-Fe(III)-oxyhydroxides, organic matter, and clay particles (Byrne and Sholkovitz, 1996;Bau and Koschinsky, 2009). This process leaves the residual water column depleted in Ce, thus creating the characteristic negative Ce 50 anomaly.…”
Section: Iron Formations As Tracers Of Seawater Redoxmentioning
confidence: 99%
“…Cerium is sensitive to redox changes and easily removed from solution as CeO 2 and/or by adsorption onto Mn-and Fe-oxyhydroxide under oxidizing conditions (Bau, 1999;Seto and Tsaku, 2008;Bau and Koschinsky, 2009 and references therein). A strong positive Ce anomaly was found in the lake water, quite different from the hydrothermal waters.…”
Section: Ce Anomalymentioning
confidence: 99%